Case Report: “Smart Palliation” and “Clepsydra Shape”: A new approach in complex congenital heart disease - Bellanti, Ermanno; Calaciura, Rita E.; Andriani, Ines; Saitta, Michele; Agati, Salvatore (Frontiers in Pediatrics, 2023)
A limiting factor in the use of vascular conduits in the Pediatric/New-Born population is their inability to grow. Many complex congenital heart diseases require palliative surgery, but the use of rigid and non-expandable conduits does not allow the structures to grow and anticipates the need for redo surgery. In newborn, a way to increase the palliation time in according with the patient’s growth is desirable. In recent years, expandable shunts (exGraft™ PECA) have been developed. In according to recent material studies, it shunt could be increasing the diameter after balloon endovascular dilatation. In this case report we describe a first case of endovascular mBT shunt expansion in a TOFAVSDc patient with trisomy 21 who went to palliative treatment for trachemalacia (non-cardiac lesion association), severe pulmonary arteries hypoplasia and low weight. This case introduces the Smart Palliation concept in the clinical scenario of selected growing patients where lifetime of BT shunt, anatomic substrates and complexity of clinical status may require an additional palliation time. The limitation for endovascular conduit expansion is the fragility of anastomosis site. Anastomosis site is a lesser strength structure of the conduit and dilatation could develop procedure complications. For this reason, in this paper, we introduced our project design: a new technique (Clepsydra Shape) that consist, before surgical implantation, in pre-expansion of the proximal and distal anastomotic part of the shunt in order to obtain an increasing of 30% size in both anastomotic side, preventing balloon stress and stretch related lesion of future balloon dilatation.